Validation of the Unilateral Cleft Lip Severity Index for Surgeons and Laypersons. Issue 9 (September 2017) - Campbell, Alex; Restrepo, Carolina; Deshpande, Gaurav; Bernstein, Sarah M.; Tredway, Caroline; Wendby, Lisa; Schonmeyr, Bjorn
Abstract : Background: Severity of the primary unilateral cleft lip/nose deformity (UCL/N) is postulated to play a key role in postoperative complications, aesthetic result, and need for secondary surgery. There is no validated and widely accepted classification scheme of initial cleft severity. The purpose of this study was to validate the Unilateral Cleft Lip Cleft Severity Index as a reliable tool for evaluating presurgical UCL/N deformity by both surgeons and laypersons. Methods: Twenty-five participants (10 surgeons and 15 laypeople) evaluated 25 sets of randomly selected presurgical standardized photographs of UCL/N patients. Each participant rated patients on a scale of 1–4 using the Cleft Severity Index. Interrater reliability for surgeons, laypersons, and all participants was determined using an intraclass correlation coefficient. Histograms and regression analysis were performed to compare average ratings between groups. Results: Interrater reliability for all groups was classified as "very good" determined by intraclass correlation coefficients of 0.837 (laymen), 0.885 (surgeons), and 0.848 (all participants). These results indicate that there was a high degree of interrater across all 3 groups and that both surgeons and laypersons can reliability rate cleft severity using the Cleft Severity Index. Conclusions: This study validates the use of the Cleft Severity Index by both surgeons and laypersons as a reliable tool for evaluating the degree of presurgical severity of patients with UCL/N. The Unilateral Cleft Lip Cleft Severity Index can thus serve as a reproducible and reliable grading system for primary UCL/N deformity and to categorize patients for future outcomes studies. Abstract : Supplemental Digital Content is available in the text.